2003
DOI: 10.1038/sj.mp.4001357
|View full text |Cite
|
Sign up to set email alerts
|

Modification of human 5-HT2C receptor function by Cys23Ser, an abundant, naturally occurring amino-acid substitution

Abstract: A human serotonin (5-HT) 2C receptor gene polymorphism leads to the substitution of cysteine for serine at codon 23 (Cys23Ser); the frequency of the Ser23 allele in unrelated Caucasians is approximately 0.13. In the present study, we assessed whether Cys23Ser could affect receptor function. The two alleles were functionally compared following expression in COS-7 cells. The constitutive activity of the receptor in an in situ reconstitution system was also evaluated following expression of each allele in Sf9 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
66
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 42 publications
11
66
2
3
Order By: Relevance
“…Therefore, this paper addresses the functional consequences of the combination of RNA editing and the C23S polymorphism in the human 5-HT 2C receptor. A recent study by Okada et al 29 demonstrated that the C23S SNP in the 5-HT 2C receptor was functional, but here we report that the C23S SNP has no functional consequences, even when expressed in the VSV backbone, the most prominent isoform in the human brain. These negative data, which were reproduced in three cell lines and two laboratories, may suggest a different strategy for future genetic studies.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…Therefore, this paper addresses the functional consequences of the combination of RNA editing and the C23S polymorphism in the human 5-HT 2C receptor. A recent study by Okada et al 29 demonstrated that the C23S SNP in the 5-HT 2C receptor was functional, but here we report that the C23S SNP has no functional consequences, even when expressed in the VSV backbone, the most prominent isoform in the human brain. These negative data, which were reproduced in three cell lines and two laboratories, may suggest a different strategy for future genetic studies.…”
Section: Discussioncontrasting
confidence: 37%
“…To address the possibility that a functional consequence could be cell type dependent, we examined constitutive activity in HEK293 cells and found no difference at multiple receptor densities. Okada et al 29 found that S23 5-HT 2C-INI receptors had increased constitutive activity compared to wild-type receptors, using in vitro reconstitution of receptors expressed in Sf9 insect cells with squid Gaq and bovine Gbg subunits. However, these differences found utilizing purified proteins in vitro are not reproduced in intact cells; our studies showed that C23 and S23 5-HT 2C receptors have similar constitutive activities in intact mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although the 5-HT2A receptor is mostly related with serotonin (5-HT) excitation within the representative motor nucleus of upper airways, lack of common polymorphisms or epigenetic changes that alter messenger RNA levels for the 5-HTR2A gene may explain the absence of association between the T102C polymorphism and OSAS in this population; it is also considered a silent polymorphism and was present in a similar proportion in the control group. 8,9,13,14 The genotype AA was significantly higher in index cases, whereas the genotypes GG/GA were higher in controls, meaning that relative to the -1438G/A polymorphism, the genotype AA may be associated with OSAS in the study population; this finding concurs with other published results. 8,9 There was a significant gender difference between index cases and controls in relation to the -1438G/A polymorphism genotypes, which was not the case with T102C polymorphism genotypes.…”
Section: Resultssupporting
confidence: 82%
“…The excitatory effects of the 5-HT2C receptor are small; although the 5-HTR2C gene polymorphism is functional, the effect of an active polymorphic allele may not be sufficient for this polymorphism to be associated with the apnea/hypopnea index (AHI) because this subtype of receptor is less dominant in the nucleus of the hyplglossus. 13,14 Conversely, a 5-HTR2A gene polymorphism has recently been found in patients with OSAS: it is defined by a T->C substitution in the nucleotide position 102 8 , and a G->A substitution in position -1438 of the promoting region of the gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation